2015
DOI: 10.1175/jas-d-15-0030.1
|View full text |Cite
|
Sign up to set email alerts
|

Superrotation in Terrestrial Atmospheres

Abstract: Atmospheric superrotation with prograde equatorial winds and an equatorial angular momentum maximum is ubiquitous in planetary atmospheres. It is clear that eddy fluxes of angular momentum toward the equator are necessary to generate it. But under what conditions superrotation arises has remained unclear. This paper presents simulations and a scaling theory that establish conditions under which superrotation occurs in terrestrial atmospheres. Whether superrotation arises depends on the relative importance of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 70 publications
1
16
0
Order By: Relevance
“…Since the pioneering work of Williams and Holloway (1982), the sensitivity of the general circulation to planetary rotation and size has been widely investigated using Earth‐like troposphere GCMs (Del Genio et al., 1993; Dias Pinto & Mitchell, 2014, 2016; Laraia & Schneider, 2015; Lu & Yamamoto, 2020; Mitchell & Vallis, 2010; Potter et al., 2014; Read et al., 2018; Y. Wang et al., 2018; Williams & Holloway, 1982). It is straightforward to introduce nondimensional parameters in idealized GCMs (Dias Pinto & Mitchell, 2014; Mitchell & Vallis, 2010) with simplified heating and friction processes.…”
Section: Introductionmentioning
confidence: 99%
“…Since the pioneering work of Williams and Holloway (1982), the sensitivity of the general circulation to planetary rotation and size has been widely investigated using Earth‐like troposphere GCMs (Del Genio et al., 1993; Dias Pinto & Mitchell, 2014, 2016; Laraia & Schneider, 2015; Lu & Yamamoto, 2020; Mitchell & Vallis, 2010; Potter et al., 2014; Read et al., 2018; Y. Wang et al., 2018; Williams & Holloway, 1982). It is straightforward to introduce nondimensional parameters in idealized GCMs (Dias Pinto & Mitchell, 2014; Mitchell & Vallis, 2010) with simplified heating and friction processes.…”
Section: Introductionmentioning
confidence: 99%
“…While early paradigms of tropical momentum transport envisioned a nearly inviscid Hadley cell decelerated by Rossby waves of extratropical origin, Lee (1999) showed that in fact, the westerly eddy forcing compensates the deceleration by the off-equatorial Hadley cell in the deep tropics. As this eddy forcing plays a key role in theories of equatorial superrotation (Hide 1969), the maintenance of the tropical momentum budget has received much attention in idealized studies of planetary atmospheres (Showman and Polvani 2011;Pinto and Mitchell 2014;Laraia and Schneider 2015). It has also been suggested that the terrestrial atmosphere might transition to a superrotating state in a much warmer climate (Caballero and Huber 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the flow in the stratosphere (particularly the middle and upper stratosphere) switches between easterly in the 1x simulation to westerly and superrotating even in the 4x simulation. Laraia and Schneider [2015] noted that equatorial upper tropospheric flow became westerly when Earth's rotation rate was slowed by a factor of 2 (i.e., a "2x" day length simulation). The vertical and latitudinal extent of the superrotating jet stream expands through the 32x simulation ( Figure 6 ), the same point at which the tropospheric westerly jet streams at mid-latitudes are entirely absent.…”
Section: Simulated Climate and Atmospheric Dynamicsmentioning
confidence: 99%